Peningkatan Minat dan Hasil Belajar Sejarah dengan Metode Pembelajaran Student Facilitator And Explaining (SFAE) Siswa Kelas XI IPS 3 SMA Negeri 1 Sutojayan - Suharti, Suharti (Universitas Nusantara PGRI Kediri, 2023)
Based on the results of observations made in Class To be able to improve student learning outcomes in solving questions about Analyzing the event of the proclamation of independence and its meaning for the social, cultural, economic, political and educational life of the Indonesian nation and to achieve learning objectives, it is necessary to improve learning by applying the Student Facilitator and Explanation (SFAE) Method. The aim of this research is to apply the Student Facilitator and Explanation Method to increase interest and learning outcomes in analyzing the event of the proclamation of independence and its meaning for the social, cultural, economic, political and educational life of the Indonesian nation among Class XI IPS 3 students at SMA Negeri 1 Sutojayan, Blitar Regency. This research uses a type of classroom action research (PTK). The research results show that the application of the Student Facilitator and Explanation Method has good success criteria. This is proven by the increase in post test scores per cycle with scores above the KKM, namely the percentage in cycle I was 65.71% and in cycle II 100%.